The incidence and clinical profile of dengue hemorrhagic fever among patients diagnosed with dengue fever in a tertiary care centre in south India - Koshy, Kiren George; Suresh, Moothezhathu Kesavadas; Suresh, Meenu Maheswari; Koshy, Deepak Iype (International Journal of Research in Medical Sciences, 2021)
Background: An understanding of factors predictive of severe forms of dengue fever would be helpful in risk stratification. The objective of the study was to determine incidence of and the factors associated with the development of dengue hemorrhagic fever (DHF) among patients admitted with dengue fever. Methods: Consenting patients were consecutively enrolled in the study and were followed forward in time to establish if they had DHF rather than milder dengue. Several factors were studied to ascertain their relation to conversion to DHF. Results: Cases included were 160 (103 males), with a mean age of 39.4 years (age range: 13-78). Fifty one (32%) developed DHF. On multivariate analysis; hepatomegaly, high alanine transaminase, low serum albumin and systolic blood pressure ≤100 mm Hg were independent predictors for the development of DHF. Conclusions: Nearly a third of patients with dengue fever develop DHF. The predictors identified, should alert the physician to this impending complication.